Tom - De Paola, Tomie (New York : Putnam & Grosset, 1997)
Aside from having the same name, Tommy and his grandfather Tom share a sense of humor.
"PaperStar."
Wilson's Children
Elem. School Library Collection
School Library Journal
3.3
K-3
Keywords: Grandfathers -- Fiction; Grandfathers -- Fiction